2002
DOI: 10.1037/0022-006x.70.4.880
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of change in prolonged exposure and cognitive-processing therapy for female rape victims with posttraumatic stress disorder.

Abstract: Curve estimation techniques were used to identify the pattern of therapeutic change in female rape victims with posttraumatic stress disorder (PTSD). Within-session data on the Posttraumatic Stress Disorder Symptom Scale were obtained, in alternate therapy sessions, on 171 women. The final sample of treatment completers included 54 prolonged exposure (PE) and 54 cognitive-processing therapy (CPT) completers. For both PE and CPT, a quadratic function provided the best fit for the total PTSD, reexperiencing, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
98
2
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(111 citation statements)
references
References 15 publications
9
98
2
2
Order By: Relevance
“…Fewer than 20 clinical trials and fewer than 10 studies examining the process of therapy and change have been reported for "uncomplicated PTSD" (Foa, Keane, & Friedman, 2000;Nishith, Resick, & Griffin, 2002), so it is understandable that the evidence base is just beginning to evolve for posttraumatic self-dysregulation. We hope this overview of the phase-oriented model and of emerging therapies for self-regulatory sequelae of trauma will encourage the development of increasingly integrative and effective trauma treatments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fewer than 20 clinical trials and fewer than 10 studies examining the process of therapy and change have been reported for "uncomplicated PTSD" (Foa, Keane, & Friedman, 2000;Nishith, Resick, & Griffin, 2002), so it is understandable that the evidence base is just beginning to evolve for posttraumatic self-dysregulation. We hope this overview of the phase-oriented model and of emerging therapies for self-regulatory sequelae of trauma will encourage the development of increasingly integrative and effective trauma treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Models that view fragmentation of episodic memory as the core of posttraumatic impairment rely upon writing or telling the personal story as a means of gaining or regaining coherent narrative autobiographical memory (Courtois, 1999;Harvey, 1996;Van der Hart et al, 1998). These approaches are not necessarily incompatible; research on process and outcome in PTSD psychotherapy is too nascent to justify definitive evidence-based guidelines for therapeutic trauma memory work (Foa, Rothbaum, & Furr, 2003;Nishith, Resick, & Griffin, 2002). Therapists therefore must gauge and be prepared to flexibly revise their approach to assisting each client with trauma memory work based upon clinical assessment of the client's self-regulation both during and between therapy sessions.…”
Section: Phase 2: Recalling Traumatic Memoriesmentioning
confidence: 99%
“…One pattern, the "steady decline" is gradual and linear, whereas the "spike" and "habituation curve" capture a brief period of symptom exacerbation that is discontinuous and curvilinear. Nishith, Resick, and Griffin (2002) examined the shape of change over the course of therapy in a sample of women with rape-related PTSD who received two empirically-supported therapies -prolonged exposure or cognitive-processing therapy. These authors used curve estimation techniques to examine whether a linear or curvilinear pattern best described the course of symptom reduction in the therapies.…”
Section: Anxiety Disordersmentioning
confidence: 99%
“…However, the most well-developed and fully researched combination therapy is Resick and Schnicke's (1992) cognitive processing therapy (CPT) for rape-related PTSD, which combines elements of cognitive therapy, exposure therapy, and AMT. CPT has demonstrated efficacy in several studies that have investigated its utility with sexual assault survivors (Nishith, Resick, & Griffin, 2002;Resick, Nishith, Weaver, Astin, & Feuer, 2002).…”
Section: Combined Treatment Approachesmentioning
confidence: 99%